2017
DOI: 10.1039/c7dt02247f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a highly dispersed CuO catalyst on CoAl-HT for the epoxidation of styrene

Abstract: A highly dispersed CuO catalyst was prepared by the deposition-precipitation method and evaluated for the catalytic epoxidation of styrene with tert-butyl hydroperoxide (TBHP) as the oxidant under solvent acetonitrile conditions. Compared with MgAl hydrotalcite (MgAl-HT)-, MgO-, TiO-, C-, and MCM-22-supported catalysts, CuO/CoAl-HT exhibited preferable activity and selectivity towards styrene oxide (72% selectivity at 99.5% styrene conversion) due to its high dispersion of CuO and surface area of Cu. The impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
3
26
0
Order By: Relevance
“…Under this condition, the SO yield can achieve 70.9% with 99.3% styrene conversion and 71.4% SO selectivity. This yield value of 70.9% is better or comparable to those of the reported heterogeneous co-balt-containing catalysts under similar reaction conditions, such as mesoporous Co3O4 (8.3%) [31], Co-NH2-KIT-6 (33.0%) [48], CoO (34.6%) [49], CoOx/TiO2/SBA-15 (54.3%) [22] and CuO/CoAl-HT (71.6%) [50].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Under this condition, the SO yield can achieve 70.9% with 99.3% styrene conversion and 71.4% SO selectivity. This yield value of 70.9% is better or comparable to those of the reported heterogeneous co-balt-containing catalysts under similar reaction conditions, such as mesoporous Co3O4 (8.3%) [31], Co-NH2-KIT-6 (33.0%) [48], CoO (34.6%) [49], CoOx/TiO2/SBA-15 (54.3%) [22] and CuO/CoAl-HT (71.6%) [50].…”
Section: Resultssupporting
confidence: 77%
“…Previous studies have demonstrated that the formation of M-peroxo species should be responsible for the SER [16,30,50,53]. Based on this understanding and the above dis- cussions, the possible reaction pathways for the SER over the Co3O4-based catalysts were reasonably proposed.…”
Section: Resultsmentioning
confidence: 80%
“…He et al. synthesized a highly dispersed CuO on CoAl‐HT (hydrotalcite) by the deposition–precipitation method and used for catalytic epoxidation of styrene with TBHP as an oxidant and acetonitrile as a solvent at 85 °C . This catalyst exhibited good activity and selectivity towards styrene oxide (72% selectivity at 99.5% styrene conversion), as compared with MgAl hydrotalcite (MgAl‐HT)‐, MgO‐, TiO 2 ‐, C‐, and MCM‐22‐supported catalysts.…”
Section: Metal Oxides and Supported Metal Oxide Catalystsmentioning
confidence: 99%
“…We can notice that the Nitmtaa@N-SBA-15 catalyst provides a quantitative conversion of styrene to cyclohexene immediately at room temperature which is much better than all reported catalysts. [45][46][47][48][49][50][51][52] While, heat at around 80 C with prolonged reaction time ($6 h).…”
Section: Styrene Epoxidationmentioning
confidence: 99%
“…Fe, Cr, Ru, Mn, Ni, with facilely accessible high oxidation states, include porphyrin transition metal complexes, and using peroxycarboxylic acids such as m-CPBA as oxygen donor, this reaction probably operates by redox mechanism involving the formation of Ni II -OOAr and Ni-Oxo activated species, which transfer the oxygen to the olen either directly or by the intermediacy of a metallacycle, a radical, cation species, or via concerted transition state. 10,49,53,54 For porphyrins complexes, this mechanism was named by Groves as oxygen-rebound mechanism. 55 In this mechanism, an oxygen atom is transferred from the oxidant to the metal ion to form metal-oxo species (M-Oxo) with high oxidation state, which in turn transfers this oxygen atom to the olenic substrate.…”
Section: Proposed Mechanismmentioning
confidence: 99%